Ultramorphological Comparison of Proboscis and Associated Sensilla of Scotogramma trifolii and Protoschinia scutosa (Lepidoptera: Noctuidae) - Chuan-Min Zhang (MDPI AG, 2021)
The proboscis is an important feeding organ for the glossatan moths, mainly adapted to the flower and non-flower visiting habits. The clover cutworm, Scotogramma trifolii Rottemberg, and the spotted clover moth, Protoschinia scutosa (Denis & Schiffermuller), are serious polyphagous pests, attacking numerous vegetables and crops, resulting in huge economic losses. However, the feeding behavior and mechanisms of the adult stage remain unsatisfactorily explored. In this study, the proboscis morphology of S. trifolii and P. scutosa are described in detail using scanning electron microscopy, with the aim of investigating the morphological differences and feeding behavior of these two species. The proboscises of S. trifolii and P. scutosa are similar in morphology and structure and are divided into three zones (Zone 1–3) based on the morphological changes of the dorsal legulae. Three sensillum types are located on the proboscises of both species, sensilla chaetica, sensilla basiconica, and sensilla styloconica. Significant differences were observed in the length of the proboscis and each zone between these two species, as well as in sensilla size and number. Based on the morphology of the proboscis and associated sensilla, S. trifolii and P. scutosa are potential flower visitors, which was also reinforced by the pollen observed at the proboscis tip. These results will strengthen our understanding of the structure of the proboscis related to the feeding behavior of Noctuidae.